PERSEPSI MUHAMMADIYAH DALAM MEMAHAMI TASAWUF - Samsidar MA (Universitas Muhammadiyah Tapanuli Selatan, 2017)
Muhammadiyah formally rejects Sufism, because Sufism, according to Muhammadiyah, is often distorted into a tarekat with very strict ritual practices. In Muhammadiyah there is no tawash-shulan, yasinan, tahlilan or manaqiban like that of NU, but it does not mean that the practices of tasawuf and dhikr are not done by the Muhammadiyah people. The practices of Sufism are acceptable to them as far as individual practice, with the aim of improving the laudable akhlaq. Muhammadiyah also strongly recommends its members to increase the prayers of sunnat, dhikr and wirid, and to promote sincere attitude in the move. Until now this attitude of life is still being carried out by the Muhammadiyah people. The results of the search on Muhammadiyah basic foundation do not found the formal concept of tasawuf as commonly done among NU, there is only substantive tasawuf or tasawuf values in accordance with the basic teachings of the Qur'an san Sunnah. Muhammadiyah as a reformist organization and renewal movement, it turns out that its characters run a fairly intense spiritual life and familiar with the world of Sufism, and provide enlightenment in the Muhammadiyah movement so that it can be one of motivation for the realization of morals and spiritul life among Muhammadiyah Persyarikatan community. It should be emphasized that Muhamadiyah is not against Sufism. Muhammadiyah precisely appreciate and put forward the practice of life based on moral and spiritual values. In the perspective of Muhammadiyah, the main foundation that underlies every human worship is the Qur'an and Sunnah, so if in the Qur'an and Sunnah there is no particular concept of a worship, Sufism for example, automatically then it should not be done. Steps to find out Muhammadiyah's perception of Sufism must refer to some basic concepts that guides and the spirit of the organization as well as a binding rule for its citizens. Some basic concepts include: 1. The basic concept in Muqodimah of Muhammadiyah's Articles of Association. 2. Basic Concept of Muhammadiyah Personality. 3. The basic concept of Muhammadiyah's Islamic Living Guidelines (PHIM) Keywords: Perception, Muhammadiyah, Understanding, Sufism